THE EFFECT OF WORK ENVIRONMENT ON EMPLOYEE JOB SATISFACTION WITH WORK COMMUNICATION AS INTERVENING VARIABLES (Case Study on Civil Servants in the General Section of the Regional Secretariat of Serdang Bedagai Regency) - Ghazali Syamni; Arilasta Irawan; Siswoyo Adi Wijaya; T.M Azani; Ikram (Universitas Efarina, 2023)
In this study, the population was JNE Customers in Tebing Tinggi City, namely 60 people. Because the target population is less than 100, the sampling technique used is the census method, where the entire population of 60 JNE Customers in Tebing Tinggi City who have made 2 deliveries will be used as the research sample. the first hypothesis is accepted, meaning that Brand Perception (X) has a positive and significant effect on Consumer Attitude (Y1). the second hypothesis is accepted, meaning that Brand Perception (X) has a positive and significant effect on the Decision to Use Services (Y2). the third hypothesis is accepted, meaning that consumer attitudes (Y1) have a positive and significant effect on the decision to use services (Y2).